SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN ALAT PERMAINAN EDUKATIF (APE) UNTUK ANAK MENGGUNAKAN METODE ANALYTIC HIERARCHY PROCESS (Science and Technology (SciTech), 2023)
The large number of educational game tools (APE) on the market, in terms of prices and types, makes it confusing to choose a truly educational game tool. One of the benefits of APE is that it can optimally develop the various potentials that children have. Therefore, a decision support system (DSS) is needed to assist in the process of obtaining educational game tools (APE) for children. Where the criteria are theme criteria with sub-criteria themes of numbers, letters, and math; safety criteria; convenience criteria with easy-to-use and easy-to-understand sub-criteria; and fun level criteria with fun playing and fun learning sub-criteria. The method used in this decision support system is the Analytic Hierarchy Process (AHP) method. The AHP method was chosen because it is very good in terms of weighting criteria and consistency. In developing the system using the rapid application development system (RAD) method. The purpose of using the RAD method is to ensure that the system meets the needs and expectations of the user. The benefit of this research is to help parents and teaching staff in early childhood education choose game tools that are truly educational for children.